LEVELS OF INTERLEUKIN-6 AND TUMOR NECROSIS FACTOR ALPHA IN PREGNANT PATIENTS WITH PREECLAMPSIA AND PATIENTS WITH NORMAL PREGNANCY - Mawardi Sarengat; Ratna Akbari Ganie; Sarma N. Lumbanraja (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Preeclampsia is a pathological condition often found during pregnancy with a prevalence of about 5-7%. Abnormal implantation, abnormal trophoblast invasion, and endothelial cell dysfunction will result in increased proinflammatory cytokines. One of preeclampsia's pathogenesis is increasing levels of TNF-alpha and IL-6. Because of this, the researchers wanted to know the level of expression of TNF-alpha and Interleukin-6 in pregnant females with preeclampsia. This was an analytical study with a case-control design, done on 30 preeclampsia patients at the Adam Malik Hospital Medan in August - October 2016, who fulfilled the inclusion criteria of the study. IL-6 and TNF-alpha level were then examined, engage ethnic by ELISA with Human Interleukin-6 QY-E04262 reagent and Human Tumor Necrosis Factor-Alfa QY-E00182 reagent. The results of IL-6 in patients with preeclampsia increased (48.60±10.85) as compared to the control (31.99±2.65). TNF-alpha levels in patients with preeclampsia also increased (79.24±10.43) compared to the control (79.24±10.43). Statistical results showed significant differences in the expression of TNF-alpha and IL-6 levels in patients with preeclampsia compared with controls (p=0.0001). In this research, there were significant differences in the expression of TNF-alpha and IL-6 levels in preeclampsia patients.